Intergenerational effects of education on risky health behaviours and long-term health - Mathias Huebener (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper estimates the causal effects of parental education on their children's risky health behaviours and health status. I study the intergenerational effects of a compulsory schooling reform in Germany after World War II. Implemented across federal states at different points in time, the reform increased the minimum number of school years from eight to nine. Instrumental variable estimates and difference-in-differences estimates reveal that increases in maternal schooling reduce children's probability to smoke and to be overweight in adolescence. The effects persist into adulthood, reducing chronic conditions that often result from unhealthy lifestyles. No such effects can be identified for paternal education. Increased investments in children's education and improvements in their peer environment early in life are important for explaining the effects. Changes in family income, family stability, fertility and parental health-related behaviours are less relevant empirically. The intergenerational effects of education on health and health-related behaviours exceed the direct effects. Studies neglecting the intergenerational perspective substantially understate the full causal effects.
Keywords: I12; I20; 330; parental education; returns to education; smoking; overweight; compulsory schooling